2013
DOI: 10.1186/1755-8794-6-16
|View full text |Cite
|
Sign up to set email alerts
|

Serum microRNAs profile from genome-wide serves as a fingerprint for diagnosis of acute myocardial infarction and angina pectoris

Abstract: BackgroundIn order to identify miRNAs expression profiling from genome-wide screen for diagnosis of acute myocardial infarction (AMI) and angina pectoris (AP), we investigated the altered profile of serum microRNAs in AMI and AP patients at a relative early stage.MethodsSerum samples were taken from 117 AMI patients, 182 AP patients and 100 age-and gender-matched controls. An initial screening of miRNAs expression was performed by Solexa sequencing. Differential expression was validated using RT-qPCR in indivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
94
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(96 citation statements)
references
References 40 publications
2
94
0
Order By: Relevance
“…Six serum miRNAs, miR-1, miR-134, miR-186, miR-208, miR-223 and miR-499, were identified as AMI biomarkers and presented significant differences between the AMI and AP cases. miR-208 and miR-499 showed higher expression in the AP cases than in the AMI cases [61] . Experimental data were obtained from microarray analysis performed on mouse model of MI [32,33] , rat model of MI [43,44] and human MI [54,58] .…”
Section: Circulating Mirnas Serum and Exosome Mirnas As Ami Biomarkersmentioning
confidence: 97%
“…Six serum miRNAs, miR-1, miR-134, miR-186, miR-208, miR-223 and miR-499, were identified as AMI biomarkers and presented significant differences between the AMI and AP cases. miR-208 and miR-499 showed higher expression in the AP cases than in the AMI cases [61] . Experimental data were obtained from microarray analysis performed on mouse model of MI [32,33] , rat model of MI [43,44] and human MI [54,58] .…”
Section: Circulating Mirnas Serum and Exosome Mirnas As Ami Biomarkersmentioning
confidence: 97%
“…14,17 However, tumors have developed various mechanisms to escape immune cell-mediated elimination, thus allowing tumor relapse. 24 Recent studies have found that tumor cells abnormally express a number of miRNAs, and this abnormal miRNA expression profile significantly contributes to tumor immune escape.…”
Section: Discussionmentioning
confidence: 99%
“…17 Total RNA was isolated from each serum sample using Trizol LS Reagent (Invitrogen, California, USA) according to the manufacturer's instructions. Briefly, 200 ml of serum or ascites was mixed with 200 ml of diethylpyrocarbonate-treated water, 200 mL of phenol and 200 ml of chloroform.…”
Section: Methodsmentioning
confidence: 99%
“…In other study of AMI patients with chest pain onset < 3h, miRNA-499 was detectable in 93% when hs-cTnT was positive only in 88%, suggesting that miRNA-499 can be a novel and sensitive biomarker for AMI (34). However, the ROC analysis in the study by Li et al showed no advantage for circulating miRNA-499 over cTnT in diagnosis of AMI (35). Interestingly, miRNA-499 levels in patients diagnosed with STEMI was significantly higher than in NSTEMI subjects, and only in STEMI group was negatively correlated with the ejection fraction (34).…”
Section: Mirna-499mentioning
confidence: 56%
“…Li et al investigated the altered profile of serum miRNAs in AMI patients at a relative early stage. They identified a profile of six serum miRNAs (miRNA-1, miRNA-134, miRNA-186, miRNA-208, miRNA-223, miRNA-499) as AMI biomarkers, and miRNA-208 and miRNA-499 in their study were surprisingly overexpressed in angina pectoris patients in comparison to AMI cases (35). In other study on relatively large cohort of 424 patients with suspected acute coronary syndrome, miRNA-208b discrimination of patients diagnosed with AMI from non-AMI was accurate (AUC = 0.82), but significantly lower than for cardiac troponi T (cTnT) (AUC = 0.95) (36).…”
Section: Mirna-208mentioning
confidence: 99%